TINJAUAN YURIDIS TERHADAP PEMELIHARAAN ANAK DIBAWAH UMUR (HAK HADHANAH ) AKIBAT SUATU PERCERAIAN BERDASARKAN KOMPILASI HUKUM ISLAM - Aldi Jaya Mandala Putra (Universitas 17 Agustus 1945 Samarinda, 2019)
ABSTRACT Legal writing (thesis) discusses the study of hadhanah (child custody) problems involving divorce participation and the legal perspective on the problem of parenting underage children. This study includes juridical normative research, data collection techniques used through literature studies both books, legislation and documents, can discuss ways to improve 12-year-old children or mumayyiz dependent in the hands, in accordance with Article 105 Compilation of Islamic Law. In Psychology, children who are closer to what is needed need attention as well as love In connection with the Hadhanah case, asking the father to ask for responsibility for the child after the divorce, he clearly agreed to the terms set out in the Marriage Law in Article 41, and could also be questioned by law, because legal reasons needed by the mother could file a lawsuit based on the Regulation of the Civil Code Article 1365 (Acts against the law) and on the basis of wan achievement. Keywords: Hadhanah Rights, Divorce